School security in the context of increasing national insecurity in Nigeria (2013)
This paper examined the rising wave of insecurity in educational institutions taking a cue from the global increase in terrorism. The paper explored the concept of terrorism looking at its meaning, development and growth and its gradual manifestation into educational institutions. The importance of the paper despite previous researches is its inclination to the educational sector as it hinges on what could be done to improve on the new wave of school killings and destruction of the future lives of students and teachers. The researchers in this study explored new ways of introducing safety regulations, training and awareness to the school system. The challenges of insecurity to the educational sector as; closure of schools for unnecessarily long periods, poor understanding of security logistics by school personnel, absence of security infrastructure in schools and poor educational policies on security were explored. The study also examined some security models that could be useful for school administrators and made recommendations. Among recommendations made include the step up in awareness creation by school and non school personnel, improved training for staff and students on identification and prevention of attacks.